Management Knowhow Spillover from Foreign Direct Investment and Local Firm’s Performance - Wanjere, M.D; Kinoti, M.; Iraki, X.N; Ogutu, M. (Mediterranean Journal of Social Sciences, 2022)
The paper investigates management knowhow spillover from foreign direct investment effect on local firms performance. Scholars seem to agree on the importance of foreign direct investment spillover for country’s growth but opinions vary regarding its impact. The study sort to establish the effect of management know spillover from FDI on performance of manufacturing firms. Empirical and theoretical literature has been reviewed on the key constructs of the study and hypothesis formulated. The reviewed literature has led to formulation of a conceptual framework showing the link among key variable of study. The study population consisted of 100 companies with at least 10 percent or more foreign ownership and registered with Kenya Association Manufacturers. The study respondents consisted of the Chief Executive Officers or representative of the participating organizations. The data was collected on management knowhow spillover from FDI and its effect on local firm performance using a questionnaire. The data was analyzed using descriptive statistics, correlation and simple regression analysis. The study established that management knowhow was significantly correlated with manufacturing firm performance and the correlation coefficient shows the relationship was weak and positive. The management knowhow accounted for 6.6% of variation in performance (R2=0.066). The corresponding model was also found to be significant (F=5.144, P<0.05) as well the coefficient for management knowhow (β=0.252, t=2.268, P<0.05). The implication of these findings is that the country policy makers should not only concern themselves with attracting FDIs, but also in ensuring that they secure the spillover to local firms. Organisation and government need to put in place policies that encourage spillovers from MNEs. Received: 6 January 2022 / Accepted: 23 February 2022 / Published: 5 March 2022